2016
DOI: 10.1080/15685551.2016.1169376
|View full text |Cite
|
Sign up to set email alerts
|

Poly(2-hydroxyethylmethacrylate-graft-folic acid), synthesis, solubility enhancement, and release dynamic of folic acid

Abstract: A series of poly (2-hydroxyethylmethacrylate-graft-folic acid) (FAHEMA) systems are synthesized by grafting of folic acid (FA) into poly (2-hydroxyethylmethacrylate) via an esterification reaction. The structure of these copolymers is confirmed by NMR and CHN analyses. The thermal behavior of these materials is characterized by DSC and TGA analyses. The surface morphology of FAHEMA films before and after the release process is examined by the SEM method. The cumulative FA released in different pH media from FA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…[8] More recently, a work by Crinivec et al reported the successful encapsulation of FA in hydrogels with the purpose of incorporating FA in food supplements, demonstrating a 30 % higher retention of FA in the human body. [9] However, all these strategies involved nonsustainable and complex synthetic processes as well as the need for chemical modifications of the FA structure.…”
Section: Introductionmentioning
confidence: 99%
“…[8] More recently, a work by Crinivec et al reported the successful encapsulation of FA in hydrogels with the purpose of incorporating FA in food supplements, demonstrating a 30 % higher retention of FA in the human body. [9] However, all these strategies involved nonsustainable and complex synthetic processes as well as the need for chemical modifications of the FA structure.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we explored the effect of counteranion exchange on the solubility and pH‐responsive properties of the synthesized copolymers. These functionalized copolymers with capabilities of cross‐linking, [35] chain extension, [31] and grafting reactions [36] could be of potential use in several industrial applications.…”
Section: Introductionmentioning
confidence: 99%